2022
DOI: 10.1111/jdv.18586
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, multicentre study to assess frailty in elderly patients with leg ulcers (GERAS study)

Abstract: Background: Although leg ulcers are a burdensome disease most common in those aged 65 years and older, frailty in this population has not yet been well established. Objectives:The aim of this study was to prospectively explore and compare the presence of frailty in elderly patients with chronic leg or foot ulcers by applying different validated frailty screening methods in three healthcare settings and to assess the feasibility of frailty screening. Methods:We compared frailty of leg ulcer patients referred to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Our study participants reported a mean global Wound-QoL score of 15 (SD=12.9), with the psyche domain having the largest mean score of 6.5 (SD=5.2). The global score is comparable to a homecare VLU population in the Netherlands who reported a mean global Wound-QoL of 15 (SD=10.4), n=20 26 . Importantly 31% of our participants reported a large impact on their QoL compared to their QoL prior to the VLU.…”
Section: Discussionsupporting
confidence: 48%
“…Our study participants reported a mean global Wound-QoL score of 15 (SD=12.9), with the psyche domain having the largest mean score of 6.5 (SD=5.2). The global score is comparable to a homecare VLU population in the Netherlands who reported a mean global Wound-QoL of 15 (SD=10.4), n=20 26 . Importantly 31% of our participants reported a large impact on their QoL compared to their QoL prior to the VLU.…”
Section: Discussionsupporting
confidence: 48%
“…To the knowledge of the authors, there are no published data of patients available in the literature evaluating the combination of both tests in urogeriatric patients. Our Medline research only revealed a few studies in non-urologic patients in which both tests were applied [16][17][18]. Among them is a recent Irish pilot study in which both tests were performed in metastatic cancer patients, but the additional value for the Mini-Cog© was not evaluated [18].…”
Section: Introductionmentioning
confidence: 99%